2020
DOI: 10.1038/s41598-020-76165-4
|View full text |Cite
|
Sign up to set email alerts
|

Inequalities in lung cancer mortality trends in Brazil, 2000–2015

Abstract: The present study was conducted to evaluate the socioeconomic inequality related to lung cancer mortality rates and trends between 2000 and 2015 according to gender in Brazil. We retrieved the death records for cases of lung cancer (ICD-10 C33 C34) from 2000 to 2015 in adults age 30 years and older in Brazilian Regions from official databases (DATASUS) and corrected for ill-defined causes. The Prais-Winsten regression method and Pearson correlation were applied. The results were considered statistically signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 29 publications
0
4
1
Order By: Relevance
“…However, the 9.35% increase in mortality from this type of cancer in the Midwest region in 2022 draws attention. A study that analyzed mortality from TBL neoplasms in the Midwest states from 2000 to 2015 found an increasing trend in only two of its four states for the female population, which presented an average annual percentage change (APC) of approximately 1.6%, and in only one state for the male population, with an APC of 0.6% [37]. Therefore, the result of the present study is atypical and deserves more careful investigation.…”
Section: Discussioncontrasting
confidence: 59%
“…However, the 9.35% increase in mortality from this type of cancer in the Midwest region in 2022 draws attention. A study that analyzed mortality from TBL neoplasms in the Midwest states from 2000 to 2015 found an increasing trend in only two of its four states for the female population, which presented an average annual percentage change (APC) of approximately 1.6%, and in only one state for the male population, with an APC of 0.6% [37]. Therefore, the result of the present study is atypical and deserves more careful investigation.…”
Section: Discussioncontrasting
confidence: 59%
“…Previous studies have focused on the incidence or mortality in some countries, such as England, 21 Belgium, 22 Brazil, 23 China and USA. 24 However, a comprehensive evaluation of the most updated incidence and mortality trends according to gender and age is lacking.…”
Section: Discussionmentioning
confidence: 99%
“…It has been determined that studies focusing on GBD generally make comparisons using SDI groups (Deng et al, 2021;Wong et al, 2017;Wang et al, 2020). Studies focusing on temporal trends in TBL cancer indicators have addressed this issue; globally (Zhou et al, 2022), USA (Zhong et al, 2019), USA and Europe (Jani et al, 2021b), China (Ni et al, 2020), China and USA (Deng et al, 2021), Brazil (Fernandes et al, 2020), Belgium (Vanthomme et al, 2021) and, Iran (Almasi et et al, 2020), it was observed that the focus was on incidence and mortality.…”
Section: Discussionmentioning
confidence: 99%